A Biography of Ferdinand and Isabella. - Stewart, Paul (1989)
Keywords: dept.his; faculty_collection; sabbatical_report

Leonard Bacon. - Davis, Hugh (1988)
Keywords: dept.his; faculty_collection; sabbatical_report

Failure of Democracy: Human Rights in the People's Republic of China. - Lee, Ta-ling (Spring; History., 1988)
Keywords: dept.his; faculty_collection; sabbatical_report

One Step Forward, One Step Back: Human Rights in the People's Republic of China in 1987/88 - Copper, John Franklin (School of Law, University of Maryland, 1989)
Keywords: 1976-2002; China; China; Human rights; Politics and government; dept.his; faculty_collection

Africans and Europeans in West Africa: Elminans and Dutchmen on the Gold Coast During the Eighteenth Century - Feinberg, Harvey M. (American Philosophical Society, 1989)
SCSU Faculty Scholar Award
Keywords: Dutch; Ghana; Elmina (Ghana); History; award_winner; dept.his; faculty_collection

Fairfield: The Biography of a Community, 1639-1989 - Farnham, Thomas J. (Published for the Fairfield Historical Society by Phoenix Pub., 1988)
Keywords: Fairfield (Conn.); History; dept.his; faculty_collection

Student Protests in Connecticut Colleges and Universities, 1701-1870: Yale College as a Case Study - Purmont, Jon Emmett (Thesis Ph. D.–Columbia University., 1988)
Keywords: Case studies; Education; Higher; Connecticut; History; History; Students; Political activity; Yale University; dept.his; faculty_collection

Reform in Reverse: Human Rights in the People's Republic of China, 1986/1987 - Lee, Ta-ling; Copper, John Franklin (School of Law, University of Maryland, 1987)
Keywords: China; Human rights; dept.his; faculty_collection

Manifest Destinies: The Usa, the Ussr - Mintz, Max M.; Bennet, John (Boston Pub. Co. ; Distributed by Field Publications, 1987)
Keywords: History; History; Russia; History; Soviet Union; United States; dept.his; faculty_collection

Upper State Street 1640-1982 - Farnham, Thomas J. (s.n., 1983)
Keywords: New Haven (Conn.); Streets; Upper State Street; dept.his; faculty_collection

Vigil in Benicarló - Azaña, Manuel (Fairleigh Dickinson University Press, 1982)
Keywords: Civil War; 1936-1939; Drama; History; Spain; dept.his; faculty_collection

Hmong and Yao: Mountain Peoples of Southeast Asia - Hamilton-Merritt, Jane (SURVIVE, 1982)
SCSU Faculty Scholar Award
Keywords: Hmong (Asian people); Yao (Southeast Asian people); Chemical warfare; award_winner; dept.his; faculty_collection

My First Days of School - Hamilton-Merritt, Jane (Simon & Schuster, 1982)
Five-year-old Kate relates the experiences of her first day in kindergarten.
Keywords: dept.his; faculty_collection

Our New Baby - Hamilton-Merritt, Jane (J. Messner, 1982)
Follows the experiences and changing feelings of a child during a year when a new baby becomes a part of his family.
Keywords: Infants; Juvenile literature; Juvenile literature; Parent and child; Juvenile literature; Siblings; dept.his; faculty_collection

Superpowers, the USA, the USSR - Mintz, Max M.; Bennet, John (HBJ Press, 1980)
Keywords: History; History; Soviet Union; United States; dept.his; faculty_collection

The nature of geography and the Schaefer-Hartshorne debate - Martin, G.J. (Reflections on Richard Hartshorne's "The nature of geography', 1989)
The tendency by geographers to cast Hartshorne as either hero or villain in modern American geography is clearly represented in this essay considering the Hartshorne-Schaefer controversy, a dispute of almost mythical proportions in the modern history of American geography. Through analysis of unpublished and published documents, the author provides us with a wealth of historical information concerning the relation between the two antagonists and the events surrounding the publication of their methodological statements. The reportage has an additional, illocutionary impact that derives from the introduction of historical specificities into the discussion of mythologized events. The description and evaluation of the events surrounding this episode in American geography, especially its portrayal of spatial analysts in the uncharacteristic role of loyal sentimentalists, will probably add fuel to the dying embers of this controversy. -from Editors
Keywords: American geography; Hartshorne; R.; Schaefer; dept.egm; geographers; historical information; illocutionary impact; methodological statement; spatial analysts; ⛔ No DOI found

Access to archives and privacy: The twenty-third international archival round table conference proceedings - Newhall, A.C. (American Archivist, 1989)
1 citations (Crossref) [2023-10-31]
Keywords: dept.his